Optimization of the cellular morphology of biaxially stretched thin polyethylene foams produced by extrusion film blowing. Issue 4 (July 2018) - Hamdi, Ouassim; Mighri, Frej; Rodrigue, Denis
This work presents the production of cellular polymer films using extrusion blowing to impose biaxial stretching on the cellular structure while processing. The materials selected are linear low-density polyethylene (LLDPE) and low density polyethylene (LDPE) as the matrix, azodicarbonamide as the chemical blowing agent, and talc as the nucleating agent. The processing parameters, namely, the temperature profile, screw speed, feed rate, take-up ratio, blow-up ratio, and the matrix composition were all optimized to produce a homogeneous cellular structure with defined morphologies. The optimized films had a thickness below 300 µm, a relative density around 0.6, a cell density above 2 × 10 6 cells/cm 3, and biaxially stretched cells with aspect ratios above 4 longitudinally and 3.8 transversally.